Kernel ridge regression improving based on golden eagle optimization algorithm for multi-class classification - Mahmood, Shaimaa; Algamal, Zakariya (Statistics, Optimization & Information Computing, 2025)
Kernel Ridge Regression combines the principles of machine learning supervision and ridge regression by employing the kernel trick. This approach is particularly effective for regression problems with non-linear relationships between inputs and outputs. The kernel trick allows Kernel Ridge Regression (KRR) to perform ridge regression by learning non-linear functions in a high-dimensional space using ridge regression’s regularization techniques. The success of KRR depends on the hyper-parameter settings, which determine the type of kernel used. Current methods for determining hyper-parameter values encounter three primary challenges: high computational costs, large memory demands, and low accuracy. This research introduces a significant improvement to the golden eagle optimization framework by incorporating elite opposite-based learning (EOBL) to enhance population diversity in the search space. We apply this strategy to efficiently select optimal hyper-parameters. Combining EOBL with KRR can lead to improved predictive accuracy. By selecting elite solutions and incorporating opposition-based methodologies, the model can circumvent local optima and broaden the range of potential solutions, leading to improved results, especially in complex datasets. The proposed enhancement to Kernel Ridge Regression was evaluated on ten publicly available multi-class datasets to demonstrate its effectiveness. The results from various evaluation criteria showed that the proposed enhancement achieved superior classification performance compared to all baseline techniques.